Context dependency of top‐down, bottom‐up and density‐dependent influences on cheetah demography. Issue 2 (4th October 2019) - Gigliotti, Laura C.; Slotow, Rob; Hunter, Luke T. B.; Fattebert, Julien; Sholto‐Douglas, Craig; Jachowski, David S.
Abstract: Research on drivers of demographic rates has mostly focused on top predators and their prey, and comparatively less research has considered the drivers of mesopredator demography. Of those limited studies, most focused on top‐down effects of apex predators on mesopredator population dynamics, whereas studies investigating alternative mechanisms are less common. In this study, we tested hypotheses related to top‐down, bottom‐up and density‐dependent regulation of demographic rates in an imperilled mesopredator, the cheetah ( Acinonyx jubatus ). We used a 25‐year dataset of lion density, cheetah density and prey density from the Mun‐Ya‐Wana Conservancy in South Africa and assessed the effects of top‐down, bottom‐up and density‐dependent drivers on cheetah survival and reproduction. In contrast to the top‐down and bottom‐up predictions, both adult and juvenile cheetahs experienced the lowest survival during months with high prey densities and low lion densities. We observed support only for a density‐dependent response in juvenile cheetahs, where they had a higher probability of reaching independence during times with low cheetah density and low prey density. We did not identify any strong drivers of litter size. Collectively, our results indicate that high apex predator abundance might not always have negative effects on mesopredator populations, and suggest that context dependency in top‐down, bottom‐up and density‐dependent factors may regulate demographic rates of cheetahs and other mesopredators. Our results highlight the complexities of population‐level drivers of cheetah demographic rates and the importance of considering multiple hypotheses of mesopredator population regulation. Abstract : The authors used a long‐term dataset to investigate drivers of cheetah reproduction and survival. They found that top‐down, bottom‐up, and density‐dependent effects on cheetah demography are context dependent and that high densities of apex predators do not always have negative effects on mesopredator demography, illustrating the importance of considering multiple drivers of mesopredator demography simultaneously.